Biliary Ascariasis Causing Obstructive Jaundice: A Case Report on ERCP-Assisted Management - Siddiqui, Ateeb; Arshad, Shaehzeen; Haider, Ehteshaam; Sajjad, Faisal (International Journal of Medical Students, 2023)
BACKGROUND: Biliary tract disorders are predominantly caused by cholelithiasis (gallstones). However, in regions endemic for parasitic infestations, or areas with poor hygiene and sanitation, hepatobiliary disorders may be due to an underlying worm infestation. THE CASE A 55-year-old female from Skardu, Pakistan, an Ascariasis-endemic area, presented to a tertiary care hospital with right hypochondrial pain and jaundice. Her condition did not respond to conservative treatment. Ultrasound (USG) and Magnetic Resonance Cholangiopancreatography (MRCP) identified multiple worms obstructing the common bile duct. Subsequently, an Endoscopic Retrograde Cholangiopancreatography (ERCP) procedure was performed, successfully retrieving the worms and achieving complete ductal clearance. The patient was discharged with oral anthelmintics and made a full recovery. CONCLUSION: This case underscores the importance of considering biliary ascariasis as a differential diagnosis for obstructive jaundice in endemic regions. MRCP emerges as a valuable diagnostic tool, providing a non-invasive and precise way to identify worm infestations of the biliary system. It effectively reduces the dependence on ERCP and its associated risks, reserving ERCP for therapeutic interventions. Equipping local healthcare centers in Ascariasis-endemic regions with the necessary resources to diagnose and treat these conditions is essential for mitigating patient suffering. This may lessen the need for travel to larger hospitals, minimising physical and financial inconveniences to the patient while also decreasing the burden on tertiary care hospitals.